Flexibility in service operations: review, synthesis and research agenda. Issue 7 (10th June 2019) - Kumar, Pradeep; Singh, Ajai Pratap
Abstract : Purpose: The purpose of this paper is to present a systematic review of flexibility, to identify the gaps in theory and to propose a future research agenda. Design/methodology/approach: This paper combines a systematic review and thematic analysis of scholarly articles of flexibility. The articles are analyzed to explicate the dynamics of flexibility in service operations. Thematic analysis was done using NVIVO 10.0 to identify key approaches, trends and future research agenda. Findings: The review reveals ten different themes that highlight the future research avenues and points out that an integrative framework to assess the field of flexibility, particularly in developing countries, is largely missing in the literature. The study also provides a set of research questions to enhance its explanatory power. Research limitations/implications: Articles that explicitly mention "flexibility" were only included, however, there may be several unexploited areas regarding the influence of different variables on flexibility. The study is based on the inductive analysis of 650 published articles on flexibility retrieved from the electronic database. The framework proposed in the study is conceptual and requires empirical testing in future research. Originality/value: The study synthesizes the flexibility literature and contributes to a set of ten distinct themes that extricate the dynamics of flexibility. The study provides a comprehensive review of the relevant articles and identifies the theoretical gaps in the research area of service operations flexibility that can be used by academia and industry for promoting flexibility.